Modeling Propp and Levi-Strauss in a Meta-Symbolic Simulation System - Klein, Sheldon; Aeschlimann, John F.; Appelbaum, Matthew A.; Balsiger, David F.; Curtis, Elizabeth J.; Foster, Mark; Kalish, S. David; Kamin, Scott J.; Lee, Ying-Da; Price, Lynne A.; Salsieder, David F. (University of Wisconsin-Madison Department of Computer Sciences, 1974)
Tests of the system include an automated generative model for a portion of Levi-Strauss' The Raw and the Cooked, and an automated generative model for Propp's Morphology of the Folktale. Output presented includes fifty Russian folktales, generated at an average rate of 128 words per second (Univac 1110/1108), including computation of plot, generation of deep structure and generation of surface text. The meta-symbolic simulation system includes a powerful behavioral simulation programming language that models, generates and manipulates events in the notation of a semantic network that changes through time, and a generalized, semantics-to-surface structure generation mechanism that can describe changes in the semantic universe in the syntax of any natural language for which a grammar is supplied. The total system has the power of at least the 2nd order predicate calculus, and will facilitate the formulation of highly abstract meta-models of discourse, including logical quantification of such models. Other features include the ability to treat objects, characters and complex actions as manifestations of the same abstract semantic unit. Extensions of the research to riddle, dream and myth generation and analysis are discussed, as well as the possibility of modelling more of the work of Levi-Strauss.